Diet-quality scores and the risk of symptomatic gallstone disease: a prospective cohort study of male US health professionals. (11th October 2018) - Wirth, Janine; Song, Mingyang; Fung, Teresa T; Joshi, Amit D; Tabung, Fred K; Chan, Andrew T; Weikert, Cornelia; Leitzmann, Michael; Willett, Walter C; Giovannucci, Edward; Wu, Kana
Abstract: Objective: To investigate the association between three diet-quality scores corresponding to adherence to healthy dietary patterns [alternate Mediterranean (aMed), Alternate Healthy Eating Index (AHEI-2010), Dietary Approaches to Stop Hypertension (DASH)] and the risk of symptomatic gallstone disease. Methods: The study comprised 43 635 men of the Health Professionals Follow-up Study—an ongoing prospective cohort study of US health professionals. Participants were free of symptomatic gallstone disease and diabetes and provided dietary information every 4 years from 1986 (baseline) until 2012. The aMed, AHEI-2010 and DASH scores were generated and associated with the risk of symptomatic gallstone disease using Cox proportional hazards regression. Results: During 716 904 person-years of follow-up, 2382 incident cases of symptomatic gallstone disease were identified. All three scores were inversely associated with risk of symptomatic gallstone disease after adjustment for potential confounders including age, smoking, physical activity, energy and coffee intake [hazard ratios (HRs) and 95% confidence intervals (CIs)] comparing the highest with the lowest quintiles: aMed: 0.66 (0.57–0.77), AHEI-2010: 0.64 (0.56–0.74) and DASH: 0.66 (0.58–0.76)]. Findings were similar after additional adjustment for body mass index and after inclusion of asymptomatic cases. Associations were stronger when analysis was restricted to cases who had undergone cholecystectomy. Conclusions: In this prospective cohort of male US health professionals, higher adherence to the aMed, AHEI-2010 and DASH diets was associated with lower risk of symptomatic gallstone disease. Dietary recommendations focusing on high-quality diets targeting symptomatic gallstone disease may lower the incidence of this prevalent disease.